An invertebrate model of the developmental neurotoxicity of insecticides: effects of chlorpyrifos and dieldrin in sea urchin embryos and larvae. - Buznikov, G A (2001)
Chlorpyrifos targets mammalian brain development through a combination of effects directed at cholinergic receptors and intracellular signaling cascades that are involved in cell differentiation. We used sea urchin embryos as an invertebrate model system to explore the cellular mechanisms underlying the actions of chlorpyrifos and to delineate the critical period of developmental vulnerability. Sea urchin embryos and larvae were exposed to chlorpyrifos at different stages of development ranging from early cell cleavages through the prism stage. Although early cleavages were unaffected even at high chlorpyrifos concentrations, micromolar concentrations added at the mid-blastula stage evoked a prominent change in cell phenotype and overall larval structure, with appearance of pigmented cells followed by their accumulation in an extralarval cap that was extruded from the animal pole. At higher concentrations (20-40 microM), these abnormal cells constituted over 90% of the total cell number. Studies with cholinergic receptor blocking agents and protein kinase C inhibitors indicated two distinct types of effects, one mediated through stimulation of nicotinic cholinergic receptors and the other targeting intracellular signaling. The effects of chlorpyrifos were not mimicked by chlorpyrifos oxon, the active metabolite that inhibits cholinesterase, nor by nonorganophosphate cholinesterase inhibitors. Dieldrin, an organochlorine that targets GABA(A )receptors, was similarly ineffective. The effects of chlorpyrifos and its underlying cholinergic and signaling-related mechanisms parallel prior findings in mammalian embryonic central nervous system. Invertebrate test systems may thus provide both a screening procedure for potential neuroteratogenesis by organophosphate-related compounds, as well as a system with which to uncover novel mechanisms underlying developmental vulnerability.